2006
DOI: 10.1152/japplphysiol.01292.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a short-term diet and exercise intervention on oxidative stress, inflammation, MMP-9, and monocyte chemotactic activity in men with metabolic syndrome factors

Abstract: Effect of a short-term diet and exercise intervention on oxidative stress, inflammation, MMP-9, and monocyte chemotactic activity in men with metabolic syndrome factors. J Appl Physiol 100: 1657-1665, 2006. First published December 15, 2005 doi:10.1152/japplphysiol.01292.2005.-The present study was designed to examine the effects of lifestyle modification on key contributing factors to atherogenesis, including oxidative stress, inflammation, chemotaxis, and cell adhesion. Obese men (n ϭ 31), 15 of whom had me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
143
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(164 citation statements)
references
References 59 publications
13
143
3
5
Order By: Relevance
“…Previous reports have linked exercise to reductions in MMP-9 levels, but have been limited to resistance training programmes in men only or exerciseplus-diet interventions in men with metabolic syndrome and children with atherosclerotic risk factors [24][25][26]. Similarly, Kadaglou et al demonstrated that in a diabetic population, a 16-week exercise programme resulted in decreased plasma levels of MMP-9 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have linked exercise to reductions in MMP-9 levels, but have been limited to resistance training programmes in men only or exerciseplus-diet interventions in men with metabolic syndrome and children with atherosclerotic risk factors [24][25][26]. Similarly, Kadaglou et al demonstrated that in a diabetic population, a 16-week exercise programme resulted in decreased plasma levels of MMP-9 [27].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, for example, of 855 enrolled participants in the HERITAGE study,8 652 had complete data; that is, the rate of missing data was 23.7%. Reports of other trials, many of them smaller, also report equivalent or higher rates of missing data68, 69, 70 or fail to report them at all 18, 71, 72, 73, 74. These studies suggest that the rate of missing data in our trial was typical for exercise training trials.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the importance of studying the postprandial state also lies in the fact that because of current dietary habits, modern humans spend most of the time in the postprandial state (de Koning and Rabelink 2002). Additionally, oxidative stress modulation by diet (Roberts et al 2002;Roberts et al 2006), may be the mechanism by which, at least partially, dietary fat may affect the development of MetS, since it has been shown that oxidative stress may be responsible for the development of MetS (Palmieri et al 2006;Furukawa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the modulation of oxidative stress by fat composition (Roberts et al 2002;Roberts et al 2006) may be the mechanism by which, at least partially, dietary fat could affect MetS development.…”
Section: Introductionmentioning
confidence: 99%